Modal Tonicization in Rock: The Special Case of the Lydian Scale - Brett Clement (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2013)
This article reexamines modal techniques in rock music, using the “problematic” Lydian mode as a test case. I argue that the Lydian scale plays a larger role in rock music than has been previously acknowledged, particularly in songs of the 1970s and ’80s. First, I outline a hierarchy of pitches and chords in the scale, which will aid in recognition of Lydian patterns in rock. Then, I address existing controversies surrounding Lydian interpretations of chord progressions, which will be viewed in light of three “tonal stability rules” necessary for convincing Lydian centricity. This will lead to a general theory of “modal tonicization” in rock music, also relevant to the remaining diatonic modes. Finally, I offer a series of analyses of songs by Todd Rundgren, Tears for Fears, and Steely Dan, which will demonstrate some of the musical and expressive potential of Lydian tonality.